Relationship between energy consumption and CO2 emissions with the human development index in american countries: an efficiency analysis using DEA (Publicaciones en Ciencias y Tecnología, 2022)
The Human Development Index (HDI) is a summary measure of the development level of each country. The objective of the research consists of an efficiency study applying Data Envelopment Analysis (DEA) and evaluating the relationship between “Fossil Energy Consumption” and “CO2 Emissions” with HDI in nine American countries with an installed hydroelectric generation capacity greater than 1000 megawatts (MW). Hydropower shows an opportunity to contribute positively to the HDI as an alternative means of electricity generation without the use of fossil fuels. HDI variable is used as the output and other two as inputs in the efficiency analysis using DEA. A total of six countries show a maximum efficiency of 100 %, with Mexico being the least efficient. In countries with less technical efficiency, it´s opportune to consider the reduction in the use of fossil fuels and establish mitigation measures in terms of CO2 emissions to improve the environment and increase human health, thus meaning an improvement in the HDI.
Keywords: energy consumption; CO2 emissions; human development index; data envelopment analysis; american countries